CONTENT, MEANS AND METHODS OF FORMATION OF COMMUNICATION CULTURE IN FUTURE FOREIGN LANGUAGE TEACHERS - Azimova Makhfuza Hasanovna (EPRA International Journal of Research and Development (IJRD), 2022)
This article is devoted to content, means and methods of formation of communication culture in future foreign language teachers. In it, one of the main requirements for future foreign language teachers is the development of communication culture, its quality, the correctness, accuracy, clarity, expressiveness of communication culture behaviors, as well as the ability to listen to one’s partner, politeness and care. The importance of the ability to build different behavioral strategies that occur in the communication process is taken into account. The article highlights the importance of using interactive educational technologies, one of the modern technologies, for successful teaching of communicative culture in English. In addition, in addition to the above-mentioned interactive educational technologies aimed at developing communication culture in future foreign language teachers, it is possible to highlight the importance of “cooperative learning” technology.